A Method for Solving Reliability of Route Travel Time. (27th April 2020) - Ma, Hongwei; Yi, Gan; Qi, Jianmin; Zhang, Zhenjie
Abstract : In order to obtain an effective method for solving route travel time reliability, this paper proposes an effective new method to calculate travel time reliability using an independent link travel time function. Based on several months of historical data, the results show that the Edgeworth expansion can better reflect travel time distribution law. In addition, travel time reliability can be calculated more conveniently by combining an approximate discretization algorithm and an empirical distribution function.